THE INFLUENCE OF MILLENIAL'S RISK PERCEPTIONS ON E-COMMERCE SHOPEE PURCHASE DECISIONS - Henilia Yulita; Koerniawan Hidajat (PRoMEDIA, 2022)
Online applications are currently an inseparable part of the role of the Millennial Generation as online shop consumers. E-commerce as an exchange of information using communication technology, with online shopping applications, purchases can be made without being limited by place. Risk perception is the consumer's perception of uncertainty and the negative consequences that may be received from online shopping, including financial risk, product risk, delivery risk, and time or convenience risk. The purpose of this study was to determine whether the millennial generation's risk perception has the ability to influence e-commerce purchasing decisions. This type of research is quantitative research by taking all millennial generations in Jakarta who have done online shopping as a population. Sampling in this study is non-probability sampling with reliance available sampling technique by relying on the presence of anyone who coincidentally meets the researcher and is deemed suitable as a sample. The results of this study state that there are no significant effects between Financial Risk and Time Convenience Risk variables on Purchasing Decision partially, but there are significant effects between Product Risk and Shipping Risk on Purchasing Decision partially, with the last there is no significant effect between Financial Risk, Product Risk, Shipping Risk, Time Convenience Risk on the Purchasing Decision simultaneously. The ongoing COVID-19 pandemic has also become one of the obstacles in the smooth running of the research process and conducting this research. Development by adding variables and research space can be considered as input for subsequent research to be carried out